Interaction of HPV with vaginal ecosystem in vaginal and cervical carcinogenesis - Bicho, Maria Clara (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Only in the 1970s and 1980s the various studies on virology and epidemiology associated with clinical evidence concluded that infection by one or more high-risk human papillomavirus (HPV) type is the leading cause of anogenital cancer. In the end of the 20th and beginning of 21st century, epidemiological studies reported the concept of high-risk HPV repeatedly and its establishment as a main risk factor for cervical cancer.[...]